2015
DOI: 10.1038/ncomms6878
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic control of transverse electric polarization in BiFeO3

Abstract: Numerous attempts have been made to realize crossed coupling between ferroelectricity and magnetism in multiferroic materials at room temperature. BiFeO 3 is the most extensively studied multiferroic material that shows multiferroicity at temperatures significantly above room temperature. Here we present high-field experiments on high-quality mono-domain BiFeO 3 crystals reveal substantial electric polarization orthogonal to the widely recognized one along the trigonal c axis. This novel polarization appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
82
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 32 publications
8
82
3
Order By: Relevance
“…A similar dependence of P s on the direction of the magnetic field was observed in BiFeO 3 [37,38]. The numerical calculations show that in both orientations that with increasing of the external magnetic field h the width of the temperature interval ΔТ SR = T 1 -T 2 decreases (Fig.…”
Section: Ugc Approved Journalsupporting
confidence: 60%
“…A similar dependence of P s on the direction of the magnetic field was observed in BiFeO 3 [37,38]. The numerical calculations show that in both orientations that with increasing of the external magnetic field h the width of the temperature interval ΔТ SR = T 1 -T 2 decreases (Fig.…”
Section: Ugc Approved Journalsupporting
confidence: 60%
“…This state is known to exhibit marginal quadratic magnetoelectric (ME) effect at low magnetic fields [12]. High magnetic fields of ∼20 T stabilize the canted antiferromagnetic (CAFM) phase as opposed to the cycloidal phase [13][14][15][16][17]. Although several groups succeeded in realizing the CAFM phase at zero field [18][19][20][21][22][23], the ME effect in this phase has not been clarified.…”
mentioning
confidence: 99%
“…The kink at ∼ 15 T indicated the existence of a magnetic transition at this field [17]. Extrapolation of the linear M -H curve at high field to zero field indicated finite offsets in the vertical axis and thus suggested that the high field phase possesses spontaneous magnetization (M S ).…”
mentioning
confidence: 99%
See 2 more Smart Citations